2004
DOI: 10.1242/jcs.01102
|View full text |Cite
|
Sign up to set email alerts
|

Proteins that bind A-type lamins: integrating isolated clues

Abstract: What do such diverse molecules as DNA, actin, retinoblastoma protein and protein kinase Cα all have in common? They and additional partners bind `A-type' lamins, which form stable filaments in animal cell nuclei. Mutations in A-type lamins cause a bewildering range of tissue-specific diseases, termed `laminopathies', including Emery-Dreifuss muscular dystrophy and the devastating Hutchinson-Gilford progeria syndrome, which mimics premature aging. Considered individually and collectively, partners for A-type la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
190
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(195 citation statements)
references
References 91 publications
(105 reference statements)
1
190
0
4
Order By: Relevance
“…In addition to participating in nuclear architecture, there is a growing body of evidence showing that lamin A/C plays a key role in gene transcription regulation, DNA repair and replication [1,3], and cell differentiation regulation [1,4,5]. The list of lamins A and C partners is regularly growing [2,[6][7][8][9], which confirms that these proteins are involved in multiple functions, some of which are still being unravelled. For instance, it has recently been shown that lamins A and C are tightly connected to the cytoskeleton, thus revealing a nuclear-cytoskeletal continuity [10].…”
Section: Introductionmentioning
confidence: 97%
“…In addition to participating in nuclear architecture, there is a growing body of evidence showing that lamin A/C plays a key role in gene transcription regulation, DNA repair and replication [1,3], and cell differentiation regulation [1,4,5]. The list of lamins A and C partners is regularly growing [2,[6][7][8][9], which confirms that these proteins are involved in multiple functions, some of which are still being unravelled. For instance, it has recently been shown that lamins A and C are tightly connected to the cytoskeleton, thus revealing a nuclear-cytoskeletal continuity [10].…”
Section: Introductionmentioning
confidence: 97%
“…Entry into and maintenance of cell cycle arrest is essential for cellular differentiation. In addition, pRB is important for muscle and fat cell differentiation (34), as well as cellular senescence (50), suggesting that deregulated pRB activity could play a role in the pathology associated with laminopathies (14,36,57,61,75,78,79).Overexpression of p16 ink4a inhibits cyclin D-dependent kinase activity leading to hypophosphorylated pRB, reduced E2F activity, and arrest in the G 1 phase of the cell cycle (60). Cells lacking pRB are refractory to arrest by p16 ink4a (8,33,38,43).…”
mentioning
confidence: 99%
“…Entry into and maintenance of cell cycle arrest is essential for cellular differentiation. In addition, pRB is important for muscle and fat cell differentiation (34), as well as cellular senescence (50), suggesting that deregulated pRB activity could play a role in the pathology associated with laminopathies (14,36,57,61,75,78,79).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the lamina, underlying the nuclear membrane, is essential for maintaining nuclear shape, spacing nuclear pore complexes, anchoring and organizing heterochromatin [1][2][3][4]. Lamina is a meshwork of nuclear-specific type V intermediate filaments (IF) called lamins, associated with the nuclear membrane, either directly or through interactions with membrane-bound proteins [2,3,[5][6][7][8]. As a basic structural unit, lamins form coiled-coil dimers that associate longitudinally to form polar head-to-tail polymers [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%